Prognostic Value of Complement Properdin in Cancer - Mangogna, Alessandro; Varghese, Praveen M.; Agostinis, Chiara; Alrokayan, Salman H.; Khan, Haseeb A.; Stover, Cordula M.; Belmonte, Beatrice; Martorana, Anna; Ricci, Giuseppe; Bulla, Roberta; Kishore, Uday (Frontiers in Immunology, 2021)
The complement system is readily triggered by the presence of damage-associated molecular patterns on the surface of tumour cells. The complement alternative pathway provides rapid amplification of the molecular stress signal, leading to complement cascade actvation to deal with pathogens or malignant cells. Properdin is the only known positive regulator of the alternative pathway. In addition, properdin promotes the phagocytic uptake of apoptotic T cells by macrophages and dendritic cells without activating the complement system, thus, establishing its ability to recognize “altered-self”. Dysregulation of properdin has been implicated in a range of pathology, leading to substantial tissue damage in the host, and in some cases, to chronic unresolved inflammation. A corollary of this may be the development of cancer. Hence, to establish a correlation between properdin presence/levels in normal and cancer tissues, we performed bioinformatics analysis, using Oncomine and UALCAN. Survival analyses were performed using UALCAN and PROGgeneV2 to assess if properdin can serve as a potential prognostic marker for human lung adenocarcinoma (LUAD), liver hepatocellular carcinoma (LIHC), cervical squamous cell carcinoma (CESC), and pancreatic adenocarcinoma (PAAD). We also analysed levels of tumour-infiltrating immune cells using TIMER, a tool for characterizing immune cell composition in cancers. We found that in LUAD and LIHC, there was a lower expression of properdin in the tumours compared to normal tissues, while no significant difference was observed in CESC and PAAD. Survival analysis demonstrated a positive association between properdin mRNA expression and overall survival in all 4 types of cancers. TIMER analysis revealed that properdin expression negatively correlated with tumour purity and positively correlated with levels of infiltrating B cells, cytotoxic CD8+ T cells, CD4+ helper T cells, macrophages, neutrophils and dendritic cells in LUAD, CESC and PAAD, and with levels of B cells, CD8+ T cells and dendritic cells in LIHC. Immunohistochemical analysis revealed that infiltrating immune cells are the most likely source of properdin in the tumour microenvironment. Thus, complement protein properdin shows promise as a prognostic marker in cancer and warrants further study.